Trillion-dollar coach : the leadership playbook from Silicon Valley's Bill Campbell - Schmidt, Eric, 1955 April 27-; Rosenberg, Jonathan, 1961-; Eagle, Alan (HarperBusiness, an imprint of HarperCollinsPublishers, 2019)
"Eric Schmidt, Jonathan Rosenberg and Alan Eagle, the team behind How Google Works, return with the story of Bill Campbell, the greatest executive business coach the world has ever seen, responsible for creating more value than just about anybody else on the planet"--